PENGEMBANGAN PERANGKAT PERKULIAHAN INOVATIF BERDASARKAN TINGKAT OTONOMI PEBELAJAR PADA PERKULIAHAN FISIKA DASAR - Abdul Salam M.; Prabowo Prabowo; Z.A. Imam Supardi (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research was intended to produce the innovative instructional materials based on the learner autonomy levels on fundamental physics lecture and also to describe the feasibility of the materials. This research was conducted in two stages. The first stage was the preparation intended to produce the innovative instructional materials. The second stage was the instructional implementation in a classroom by using the pretest and posttest group design. The data of research results showed that the developed instructional materials were declared valid according to the expert judgment with good category on the whole. The developed instructional materials also fulfilled the practical criteria based on (a) the application of the lesson plan in classroom reaching 100% with the quality of very good category, and (b) the students activities were suitable with the requirement of every stage of the lesson plan. Furthermore, the developed instructional materials were also declared effective based on (a) the assessment of the students learning outcome giving the learning mastery of 100%, while the mastery of achievement indicator of basic competence being 100%, and (b) the students response to the instruction in the forms of interest and motivation including the aspects of attention, relevance, self-confidence, and satisfaction, all of which being of good category. Based on the findings of the research, it can be concluded that the developed instructional materials based on the learner autonomy levels were declared feasible (valid, effective, and practical) to be used on fundamental physics lecture Penelitian ini bertujuan untuk menghasilkan perangkat perkuliahan inovatif berdasarkan tingkat otonomi pebelajar pada perkuliahan fisika dasar dan juga untuk mendeskripsikan kelayakan perangkat perkuliahan tersebut. Penelitian ini dilaksanakan dalam dua tahap. Tahap pertama adalah persiapan; bertujuan untuk menghasilkan perangkat. Tahap kedua adalah implementasi  perkuliahan di kelas yang menggunakan rancangan pretest and posttest group design. Data hasil penelitian menunjukkan bahwa perangkat perkuliahan yang dikembangkan dinyatakan valid berdasarkan hasil penilaian pakar yang kesemuanya berkategori baik. Perangkat perkuliahan hasil pengembangan juga memenuhi kriteria praktis berdasarkan (a) keterlaksanaan RPP sebesar 100% dengan kualitas keterlaksanaan berkategori sangat baik, dan (b) aktivitas mahasiswa sesuai dengan tuntutan dari setiap tahapan perkuliahan yang direncanakan. Lebih lanjut perangkat perkuliahan yang dikembangkan juga dinyatakan efektif berdasarkan (a) hasil belajar mahasiswa yang memberikan ketuntasan sebesar 100%, dengan ketuntasan indikator ketercapaian kompetensi dasar 100%, dan (b)  respon mahasiswa terhadap perkuliahan berupa minat dan motivasi yang meliputi aspek perhatian, relevansi, kepercayaan diri, dan kepuasan, yang semuanya berkategori baik. Berdasarkan temuan-temuan hasil penelitian, dapat disimpulkan bahwa perangkat perkuliahan berdasarkan tingkat otonomi pebelajar yang dikembangkan dinyatakan layak (valid, efektif dan praktis) untuk digunakan dalam perkuliahan fisika dasar